Carbon dioxide adsorption based on porous materials. Issue 21 (31st March 2021) - Sai Bhargava Reddy, M.; Ponnamma, Deepalekshmi; Sadasivuni, Kishor Kumar; Kumar, Bijandra; Abdullah, Aboubakr M.
Abstract : Global warming is considered one of the world's leading challenges in the 21st century as it causes severe concerns such as climate change, extreme weather events, ocean warming, sea-level rise, declining Arctic sea ice, and acidification of oceans. Abstract : Global warming due to the high concentration of anthropogenic CO2 in the atmosphere is considered one of the world's leading challenges in the 21 st century as it leads to severe consequences such as climate change, extreme weather events, ocean warming, sea-level rise, declining Arctic sea ice, and the acidification of oceans. This encouraged advancing technologies that sequester carbon dioxide from the atmosphere or capture those emitted before entering the carbon cycle. Recently, CO2 capture, utilizing porous materials was established as a very favorable route, which has drawn extreme interest from scientists and engineers due to their advantages over the absorption approach. In this review, we summarize developments in porous adsorbents for CO2 capture with emphasis on recent studies. Highly efficient porous adsorption materials including metal–organic frameworks (MOFs), zeolites, mesoporous silica, clay, porous carbons, porous organic polymers (POP), and metal oxides (MO) are discussed. Besides, advanced strategies employed to increase the performance of CO2 adsorption capacity to overcome their drawbacks have been discoursed.